Ophthalmological examination and VEPs in preterm children with perinatal CNS involvement - Kuba, Miroslav; Liláková, Dana; Hejcmanová, Dagmar; Kremláček, Jan; Langrová, Jana; Kubová, Zuzana (Documenta ophthalmologica, 2008)
Five children with a history of preterm birth (mean gestational age of 27 weeks; birth weight 870-1,380 g) and perinatal post-hemorrhagic hydrocephalus were examined ophthalmologically at ages ranging from 4-11 years. An extended visual evoked potentials (VEPs) examination was simultaneously performed, using pattern-reversal, motion-onset, and cognitive visual stimuli. Although 3 of the 10 eyes displayed about normal visual acuity (> or =0.9), all of the examined eyes were abnormal for at least one variant of the tested VEPs. Pathological changes in VEPs (missing responses, shape abnormalities due to delayed VEPs maturation, prolonged peak latencies, and reduced amplitudes) were roughly proportional to both gestational age and reduction in visual acuity. A more severe pathology was found in the motion-onset VEPs (in all five subjects - nine eyes) when compared to the pattern-reversal VEPs (in four subjects - eight eyes). These observations suggest that the magnocellular system/dorsal stream of the visual pathway (which is particularly activated in response to motion stimuli) may be more frequently affected in preterm children than the parvocellular system/ventral stream (tested mostly by the standard pattern-reversal VEPs). This pilot study may encourage further testing of the combined pattern and motion-related VEPs examinations in preterm children as a way of detecting hidden cortical/cerebral visual impairment (CVI).
Keywords: gestační stáří; financování organizované; dítě; předškolní dítě; novorozenec; Central Nervous System Diseases; Gestational Age; Refraction, Ocular; Visual Pathways; refrakce oka; zrakové korové centrum; lidé; Infant, Newborn; novorozenec nedonošený; Infant, Low Birth Weight; Pilot Projects; pilotní projekty; Infant, Premature; zrakové dráhy; Financing, Organized; novorozenec s nízkou porodní hmotností; Evoked Potentials, Visual; nemoci centrálního nervového systému; Child, Preschool; Child; zraková ostrost; Visual Acuity; Visual Cortex; zrakové evokované potenciály; Humans